Sensory urban mapping: a case study of Istiklal Street, Istanbul with the method of 'sensewalking' - Kartal, Asiye Nisa (2021)
The 'sensory' plays a vital role in examining human and world interrelations if often overlooked. This thesis aims to have a new understanding of Istiklal Street, Istanbul, through the area's sensory qualities. The research is ground on a 'phenomenological' approach and intends to move beyond the urban visual experiences by looking into the area's multi-sensory experiences. The practice of 'sensewalking' has been used in research to cope with visually-oriented urban assessments. This investigation, which is structured with a qualitative lens to discover the Street's sensory aspects, would be worthwhile primarily for the fields of architecture, urban sensory design.